Avatar, the last airbender. North and south. Part three - Yang, Gene Luen (Dark Horse Books, 2017)
Fire Lord Zuko and Earth King Kuei arrive in the kingdom of the Southern Water Tribe where the council meets to confirm Malina and Hakoda's unification plans. But then Gilak escapes prison and kidnaps the Earth King. Now Katara will have to step up to save her home and family.